1985
DOI: 10.1111/j.1528-1157.1985.tb05658.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism and Epilepsy

Abstract: There is a scarcity of population-based epidemiological investigations concerning the prevalence of epilepsy among alcoholics, and of alcoholism among epileptic patients. Available data seem to suggest that the prevalence of epilepsy among alcoholics is at least triple that in the general population, and that alcoholism may be more prevalent among epileptic patients than in the general population. The term "alcoholic epilepsy" has been used with varying definitions in different investigations. It is suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 103 publications
0
43
0
3
Order By: Relevance
“…This is of interest as excessive alco hol consumption can increase the frequency of seizures and precipitate status epilepticus in epileptic patients [Chan, 1985], Available evidence suggests that the prevalence of epi lepsy among alcoholics is at least 3 times that of the general population and that alcohol ism may be more prevalent among epileptic patients than in the general population [Lit tle and Gayle, 1980], Hence the combination of alcoholism and epilepsy constitutes a seri ous medical and social problem and deserves special attention. Annegers et al [1984] demonstrated an increased incidence of myocardial infarction in patients with both idiopathic and symp tomatic epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…This is of interest as excessive alco hol consumption can increase the frequency of seizures and precipitate status epilepticus in epileptic patients [Chan, 1985], Available evidence suggests that the prevalence of epi lepsy among alcoholics is at least 3 times that of the general population and that alcohol ism may be more prevalent among epileptic patients than in the general population [Lit tle and Gayle, 1980], Hence the combination of alcoholism and epilepsy constitutes a seri ous medical and social problem and deserves special attention. Annegers et al [1984] demonstrated an increased incidence of myocardial infarction in patients with both idiopathic and symp tomatic epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these 21 returned to normal in under 2 weeks, two had a previous history of unprovoked seizures and three had a history of head injury, leaving 12 patients with persistently abnormal records. Other studies agree with this finding of interictal epileptiform activity (IEA) in less than 10 per cent of the EEG records of persons with seizures occurring only after alcohol withdrawal, in contrast with IEA in the EEG records of 50 per cent of patients with seizures not precipitated by alcohol withdrawal (Giove and Gastaut, 1965;Deisenhammer et al, 1984;Chan, 1985).…”
Section: Electroencephalographic Findings In Alcohol Withdrawalmentioning
confidence: 65%
“…In the remainder, head injuries sustained as a consequence to intoxication and poor compliance with prescribed antiepileptic drugs (AEDs) appeared to be important mechanisms (Earnest and Yarnell, 1976;Hillbom, 1980). In other studies the proportion of seizures caused by alcohol withdrawal ranged from 0 to 24 per cent (Chan, 1985). This wide range is a result of studying different populations and differing selection criteria.…”
Section: Alcohol Withdrawal Seizuresmentioning
confidence: 96%
“…3,8,12) If hemorrhagic contusion or intraparenchymal hemorrhage combined with CSDH, seizure occurrence was elevated up to 40%. 4) However, the present case did not have any above mentioned risk factors on past history. Also, admission CT did not revealed any other hemorrhage but CS-DH or destructive lesion of the dura and brain parenchyma.…”
Section: Discussionmentioning
confidence: 85%